Mitos Genjer-Genjer: Politik Makna dalam Lagu - Utan Parlindungan (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
Merely based on the ideological struggle, the arts play an important role, especially as a means of forming unisonality, group identiﬁ cation and emotional bridge between individuals in bringing “sense” that the goals of power may easily be achieved. No exception of music; it deliberately created and disseminated for the sake of its own nature. However, power is not as universal as music; making a claim toward music (songs) in the risk of political contestation may produce ambivalence meanings (ambiguity). In one hand, music tends to be sacred, but a moment later, it is more vulnerable to be alienated or marginalized. In some cases, the practice of politicization oft en ends up banning music and tragedy.